Financial Literation and Investment Decision Behavior of Entrepreneurs in Bali - Ni Putu Yeni Astiti; G. Oka Warmana; Mifthahul Hidayah (International Journal of Applied Business and International Management, 2019)
This study uses three dimensions of financial literacy, namely financial knowledge, financial behavioral and financial attitude. This study examines the effect of financial literacy on investment decision behavior. This research takes data from entrepreneurs in Bali, Indonesia. Bali has an entrepreneurial ratio to population that is higher than the national average. The regression results show (1) financial knowledge does not affect investment decision making, (2) financial behavior does not affect investment decision making, (3) financial attitude has a positive effect on investment decision making. These results indicate that the financial knowledge and how someone behaves about finance does not have an impact on investment decisions as an entrepreneur. Entrepreneurs in our sample may become an entrepreneur even though does not have sufficient financial knowledge and has not shown good financial management behavior.